Influence of Collective Leadership and Interpersonal Relationships on the Performance of Commission Members - Hars Seasar Valentino; Jacinta Winarto (Jurnal Informatika Ekonomi Bisnis, 2026)
This study examines the influence of collective leadership, interpersonal relations, and performance. The object of this study is the members of the Commission of the Cimuning Congregation of the Pasundan Christian Church. In this study, the researcher intends to look more deeply into the influence of collective leadership and interpersonal relations on the performance of commission members. The researcher used a quantitative approach; the population of the study is the commission members; the sample amounted to 35 people. The sample selection used a purposive sampling technique. The data were processed using the Statistical Product and Service Solutions application. Through SPSS, the researcher conducted a multiple linear regression analysis and tested the hypotheses. The results of the study state that, partially, collective leadership does not have an effect on the performance of commission members. Meanwhile, interpersonal relations have a positive effect on the performance of commission members. The results of the study give an indication that collective leadership cannot become a single variable in influencing the performance of commission members. Collective leadership requires interpersonal relations in the context of this study. In addition, the better the interpersonal relations, the more the performance of commission members increases. This indication can become a practical suggestion for the GKP Cimuning Commission to be able to strengthen interpersonal relations.